New genus and species of Neotropical robber flies (Diptera, Asilidae, Asilinae) - Artigas, Jorge N.; Vieira, Rodrigo (Zootaxa, 2014)
A new genus and species of Papaverellus aureocingulatus from Brazil, belonging to the asilid subfamily, is described and illustrated. Photographs of the habitus of the male and female in lateral view, and male terminalia in ventral view are provided. The systematic position of Papaverellus gen. nov. is suggested and will be addressed in a future paper.